2022
DOI: 10.1002/ajpa.24497
|View full text |Cite
|
Sign up to set email alerts
|

An isotope signature for diffuse idiopathic skeletal hyperostosis?

Abstract: Objectives Diffuse idiopathic skeletal hyperostosis (DISH) has recurrently been associated with a rich diet (high in protein and higher trophic level foods); however, very few studies have investigated this link using carbon and nitrogen (δ13C and δ15N) stable isotope analysis. This paper explores the relationship between DISH and diet in two Roman urban communities by analyzing individuals with and without DISH. Materials and methods δ13C and δ15N analysis carried out on collagen from 33 rib samples (No DISH:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
0
0
0
Order By: Relevance
“…Furthermore, other types of pathologies that show ossification of ligaments and joints are also sexually dimorphic. Pathologies such as diffuse idiopathic skeletal hyperostosis (DISH) (Castells Navarro et al, 2022; Verlaan et al, 2007) and ankylosing spondylitis (AS) (Duyar, 2019) are more commonly found in males than females. Both DISH and AS include the ossification of spinal ligaments (Castells Navarro et al, 2022; Duyar, 2019), and AS specifically can impact the SI joints (Duyar, 2019; Šlaus et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other types of pathologies that show ossification of ligaments and joints are also sexually dimorphic. Pathologies such as diffuse idiopathic skeletal hyperostosis (DISH) (Castells Navarro et al, 2022; Verlaan et al, 2007) and ankylosing spondylitis (AS) (Duyar, 2019) are more commonly found in males than females. Both DISH and AS include the ossification of spinal ligaments (Castells Navarro et al, 2022; Duyar, 2019), and AS specifically can impact the SI joints (Duyar, 2019; Šlaus et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pathologies such as diffuse idiopathic skeletal hyperostosis (DISH) (Castells Navarro et al, 2022; Verlaan et al, 2007) and ankylosing spondylitis (AS) (Duyar, 2019) are more commonly found in males than females. Both DISH and AS include the ossification of spinal ligaments (Castells Navarro et al, 2022; Duyar, 2019), and AS specifically can impact the SI joints (Duyar, 2019; Šlaus et al, 2012). In other words, males are more prone to joint ossification than females are, and SI joint fusion may not be the exception to the rule.…”
Section: Discussionmentioning
confidence: 99%